Genome-wide association study identifies eight new risk loci for polycystic ovary syndrome - Shi, Yongyong; Zhao, Han; Shi, Yuhua; Cao, Yunxia; Yang, Dongzi; Li, Zhiqiang; Zhang, Bo; Liang, Xiaoyan; Li, Tao; Chen, Jianhua; Shen, Jiawei; Zhao, Junzhao; et al. (Nature genetics, 2012)
Zi-Jiang Chen and colleagues report a genome-wide association analysis for polycystic ovary syndrome (PCOS) in Han Chinese. They identify eight new susceptibility loci for PCOS in this population. Following a previous genome-wide association study (GWAS 1) including 744 cases and 895 controls, we analyzed genome-wide association data from a new cohort of Han Chinese (GWAS 2) with 1,510 polycystic ovary syndrome (PCOS) cases and 2,016 controls. We followed up significantly associated signals identified in the combined results of GWAS 1 and 2 in a total of 8,226 cases and 7,578 controls. In addition to confirming the three loci we previously reported, we identify eight new PCOS association signals at P < 5 × 10 −8 : 9q22.32, 11q22.1, 12q13.2, 12q14.3, 16q12.1, 19p13.3, 20q13.2 and a second independent signal at 2p16.3 (the FSHR gene). These PCOS association signals show evidence of enrichment for candidate genes related to insulin signaling, sexual hormone function and type 2 diabetes (T2D). Other candidate genes were related to calcium signaling and endocytosis. Our findings provide new insight and direction for discovering the biological mechanisms of PCOS.